2022
DOI: 10.3389/fimmu.2022.893914
|View full text |Cite
|
Sign up to set email alerts
|

GSDMD contributes to myocardial reperfusion injury by regulating pyroptosis

Abstract: BackgroundGasdermin D (GSDMD) plays an essential role in the pathway of pyroptosis. However, whether GSDMD participates in myocardial ischaemia/reperfusion injury (MI/RI) remains poorly understood.MethodsSerum levels of GSDMD and IL-18 in ST-segment elevation myocardial infarction (STEMI) patients were measured by ELISA. The expression of GSDMD and GSDMD N-terminal (GSDMD-NT) in vivo and in vitro was assessed by western blot and immunofluorescence staining. GSDMD-/- mice and wild type (WT) mice were induced MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Our results showed that knockdown of GALNT6 significantly increased the expression of inflammatory cytokines IL-1b, IL-18, IL-6 and TNF-a in PDAC cells. In additionally, GSDMD, the executor of pyroptosis, can be cleave by activated caspase-1 to generate GSDMD-N, which perforates the cell membrane and releases the IL-1b, IL-18, and other pro-inflammatory cytokines into the extracellular matrix (42). Here, we found that knockdown of GALNT6 significantly increased the expression of GSDMD in PDAC cells.…”
Section: Discussionmentioning
confidence: 58%
“…Our results showed that knockdown of GALNT6 significantly increased the expression of inflammatory cytokines IL-1b, IL-18, IL-6 and TNF-a in PDAC cells. In additionally, GSDMD, the executor of pyroptosis, can be cleave by activated caspase-1 to generate GSDMD-N, which perforates the cell membrane and releases the IL-1b, IL-18, and other pro-inflammatory cytokines into the extracellular matrix (42). Here, we found that knockdown of GALNT6 significantly increased the expression of GSDMD in PDAC cells.…”
Section: Discussionmentioning
confidence: 58%
“…Our ICrisk signature has integrated 7 IRGs (ARNTL, GSDMD, HAPLN3, IRX3, N4BP2L1, NUB1, PARP11). A subset of these identified genes are not solely defined to be associated with carcinogenesis but rather to play a regulatory role in non-malignant physiological or pathological processes, such as ARNTL controlling circadian rhythms [ 20 ], GSDMD regulating inflammatory responses in cardiac and lung injury pyroptosis [ 21 , 22 ], and IRX3 regulating obesity-related metabolism [ 23 ]. In recent years, studies have started supporting their roles in cancer pathology ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain functional information at the cellular level, typically genes associated with cell death, pyroptosis, or apoptosis are endogenously expressed. For instance, GSDMD N‐terminal (GSDMD‐NT) could induce pyroptosis, 78,79 and P21 induces cell proliferation inhibition and senescence 80,81 . Besides, chemical‐genetic cell ablation strategies such as the NTR‐MTZ system in zebrafish, and the DT‐DTR system in mammals also work efficiently under spatial and temporal control 82,83 …”
Section: In Vivo Gene Manipulation By the Dual‐recombinase Systemsmentioning
confidence: 99%